Analysis of total phenolic compounds in tea and fruits using diazotized aminobenzenes colorimetric spots. (1st December 2020) - Abdel Azeem, Sami M.; Al Mohesen, Ibrahem A.; Ibrahim, Ahmed M.H.
Highlights: New colorimetric Spots for total phenolic compounds (TPCs). Fast and reliable digital-image based (DIB) method. Application to TPCs determination in tea and fruits. Comparison to the reference Folin-Ciocalteu method. Abstract: The present work describes a novel and rapid approach for evaluating total phenolic compounds (TPCs) in tea and fruits using colorimetric spots and the digital image-based (DIB) method. Colorimetric spots were formed by reacting diazotized aminobenzenes namely sulfanilic acid, sulfanilamide, or aniline with TPCs in the extract to form an azo dye. The limit of detection (LOD) was 6.5, 5.5, or 5.1 mg GAE (gallic acid equivalent) L −1 and the analytical range was 25–500, 20–500, or 18–200 mg GAE L −1, respectively. Correlation with the Folin-Ciocalteu assay was significant (Pearson coefficient, R = 0.970–0.991) while the antioxidant activity assay was moderate to high (R = 0.737–0.977). The method developed was successfully applied to the analysis of tea and fruits and showed RSD (n = 3) not exceeding 9.6, 8.5, and 9.7%, respectively. Ecologically, the DIB method developed could determine the variation of TPCs within cultivars and was found to be strongly dependent on the growing environment.